The Importance of Neuropsychomotor Development Between 0-2 Years - I.M. Fintina; B.N. Stark (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The present research wanted to demonstrate and support the importance of the neuropsychomotor development in optimal conditions of a non-disabled child in the first 2 years of life as well as the importance of the intervention through a series of stimulation techniques, methods and movement games. In order to carry out the research, a series of initial, intermediate and final tests were used to see the evolution in the age stages. The tests used were: evaluation of physical development, evaluation of archaic reflexes, evaluation of pre-tension, evaluation of balance, Denver Test- evaluation of slowing of internal development and Portage Test - evaluation of chronological and biological age of the child. Following the application of the therapeutic techniques and methods, the objectives set either at the general level or at the level of each stage have been met to a satisfactory extent.